مكافحة تمويل الإرهاب على مستويين الدولي و الداخلي - بو عبسة, عمر (My University, 2019)
ملخص: مكافحة تمویل الإرهاب على المستویین الدولي والداخلي تعتبر جریمة تمویل الإرهاب التحدي الأكبر الذي یواجه المجتمع الدولي والداخلي باعتبارها من أخطر الج ا رئم المهددة للأمن والسلم الدولیین لاسیما بعد تجاوز آثار نشاطها للحدود الوطنیة، الأمر الذي استدعى إتحادا دولیا تحت مظلة أممیة للحیلولة دون إنتشارها. ولعل م ا رقبة اتجاهات وحركة النقل المادي للأموال یؤدي إلى حد كبیر إلى القضاء على الجریمة الإرهابیة أو الحد منها، وهو ما جعل الدول أثناء مواجهتها للإرهاب تتخذ ق ا ر ا رت مهمة بشأن ضبط وتفعیل أنظمتها الرقابیة من أجل تجفیف منابع تمویل الإرهاب. وقد استقر العالم على أن أفضل وسیلة لتجفیف منابع تمویل الإرهاب هي التعاون فیما بین دوله في مختلف المجالات وتعزیز ذلك من خلال تنسیق الجهود بین سائر الهیئات والمنظمات الدولیة المعنیة بمجال المكافحة مع تفعیل تبادل المعلومات بین الأجهزة الوطنیة المختصة لقطع الطریق عن ممولي الجماعات الإرهابیة. كلمات مفتاحیة: تمویل – الإرهاب – تجفیف – منابع – الشبهة – الجریمة – الجهود – المصرفیة – الأجهزة – التحریات- الأموال – تجمید – تبییض. Abstract: The crime of financing terrorism is the biggest challenge facing the international and internal community as one of the most serious crimes against international peace and security, especially after the effects of its activities on the national borders, which called for international unity under an international umbrella to prevent its spread. Monitoring the trends and movement of physical transport of funds largely leads to the elimination or reduction of terrorist crime. This is why, in the face of terrorism, States have made important decisions regarding the control and enforcement of their regulatory systems in order to dry up the sources of terrorist financing. The world has determined that the best way to drain the sources of terrorist financing is to cooperate among its countries in various fields, and to strengthen this through coordination of efforts among other international bodies and organizations concerned with combating terrorism, and to activate the exchange of information among the competent national bodies. Keywords: Financing - Terrorism - Drying - Sources - Suspicion - Crime - Efforts - Banking - Devices - Investigation - Funds - Freezing - Bleaching
التمويل-الإرهاب -التحقيق -منابع- الأموال -التحريات- الجهود-الشبهة
Keywords: الكلمات المفتاحية: الإرهاب التمويل- التحقيق - الشبهة -المصرفية